Sistem Informasi Akademik Santri Berbasis Web di Pondok Pesantren - Ade Sutedi; Yosep Septiana; Rifki Abdul Halim (Institut Teknologi Garut, 2021)
Islamic boarding schools are non-formal educational institutions with the aim of studying, interpreting, exploring, animating, and applying Islamic teachings by emphasizing the importance of religious ethics as guidelines for daily behavior. The Santri Academic Information System is needed to make it easier for parents of students and boarding school administrators because there are problems, Islamic boarding schools still use conventional systems in terms of academic information, and it is difficult to make payments and provide information to parents of students during this pandemic, so an information system is designed student academics combined with a payment system. With the existence of this Santri Academic Information System, work can be made more efficient, which before the existence of this student academic information system, business processes that were running were still using conventional methods. This study aims to design an academic information system for students in Islamic boarding schools. The methodology used is the Rational Unified Process, using four stages, namely inception, elaboration, construction, and transition using the Unified Modeling Language modeling, and using the blackbox testing method. The product of this research is the creation of a Web-Based Student Academic Information System. The contribution of this research is that this information system can help the community, especially the parents of students in searching for academic information on students at the AL Halim Garut Islamic boarding school. Garut can be a model for other Islamic boarding schools.